A Dollar for Your Thoughts: Feedback-Conditional Rebates on eBay - Cabral, Luís; Li, Lingfang (Ivy) (Management Science, 2015)
We run a series of controlled field experiments on eBay where buyers are rewarded for providing feedback. Our results provide little support for the hypothesis of buyers’ rational economic behavior: the likelihood of feedback barely increases as we increase feedback rebate values; also, the speed of feedback, bid levels, and the number of bids are all insensitive to rebate values. By contrast, we find evidence consistent with reciprocal buyer behavior. Lower transaction quality leads to a higher probability of negative feedback as well as a speeding up of such negative feedback. However, when transaction quality is low (as measured by slow shipping), offering a rebate significantly decreases the likelihood of negative feedback. All in all, our results are consistent with the hypothesis that buyers reciprocate the sellers’ “good deeds” (feedback rebate, high transaction quality) with more frequent and more favorable feedback. As a result, sellers can “buy” feedback, but such feedback is likely to be biased. Data, as supplemental material, are available at http://dx.doi.org/10.1287/mnsc.2014.2074 . This paper was accepted by Teck-Hua Ho, behavioral economics.